HUBUNGAN ANTARA PENGETAHUAN ORANG TUA TENTANG KESEHATAN GIGI DAN MULUT DENGAN KEJADIAN KARIES GIGI PADA ANAK DI SDN V JATEN KARANGANYAR - Yulianti, Rizka Puji; Muhlisin, Abi (Universitas Muhammadiyah Surakarta, 2011)
Dental Caries is an infectious disease that destroy the tooth structure and cause cavities. At the age of 6 – 12 years is needed more intensive treatment because at the age in case of replacement teeth and growth of new teeth. The role of parents is required in the sense, warn, and provide facilities to the children so that children can maintain the cleanliness of teeth and mouth and has a substantial role in preventing the accumulation of plaque and the incidence of caries in the children. Knowledge of parents is very important in establishing the behaviours that support or not support the child’s oral hygiene. The aims this research is to know relation knoeledge of parents about tooth and mouth health to incidence dental in childrens in SDN V Jaten of Karanganyar. The method research used is explanatory with design research is crocc-sectional to get describe about level knowledge of parents about tooth and mouth health to incidence of dental in childrens. The research cariied out in SDN V Jaten Karanganyar and lived of students with number sample is 70 responden, that is mother from student at I – VI. Technique of sampling used is total sampling. Technique of data collection used is quistioner and observation sheet. The analysis data used is kolmogorov – smirnov test. The result showed that (1) the level of material knowledge about tooth and mouth health in SDN V Jaten Karanganyar majority both categories as many as 45 people (64,3%). (2) majority of student in SDN V Jaten Karanganyar that is experience of dental as many as 49 people (70%). (3) Based on the result of hypothesis providable value of Z = 1,435 and p-value = 0,033. P-Value